2019
DOI: 10.2147/cmar.s191637
|View full text |Cite
|
Sign up to set email alerts
|

<p>Construction and validation of a seven-microRNA signature as a prognostic tool for lung squamous cell carcinoma</p>

Abstract: Objective: The aim of this study was to construct and validate a microRNA (miR)-based signature as a prognostic tool for lung squamous cell carcinoma (LUSC). Materials and methods: With the use of mature miR expression profiles downloaded from The Cancer Genome Atlas database, we identified differentially expressed miRs between LUSC and matched healthy lung tissue. Thereafter, we carried out an evaluation of the association of differentially expressed miRs with overall surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…This is the first report linking hsa_miR_5701 to neurological disease. It has already been linked to prognosis of patients with lung squamous cell carcinoma ( Gan et al, 2019 ), and it can inhibit the proliferation of cervical cancer cells ( Pulati et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is the first report linking hsa_miR_5701 to neurological disease. It has already been linked to prognosis of patients with lung squamous cell carcinoma ( Gan et al, 2019 ), and it can inhibit the proliferation of cervical cancer cells ( Pulati et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…We confirmed that the overexpression of POSTN can be identified as the target to predict shorter survival times in LUSC. In addition, has-miR-30e-3p was downregulated in LUSC tissues, which was proved to be strongly related to staging, poor survival, and differentiation [ 47 50 ]. However, there is no evidence suggesting that has-mir-144-3p and has-mir-30e-3p regulate POSTN expression in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this might indicate that this LLPS-related gene signature is still robust in different populations and suitable for different platforms. In some previous studies ( 30 , 31 ), univariate and multivariate Cox regression analyses were used but lack of LASSO analysis to create the prognostic gene signatures. However, these previous studies may encounter overfitting problems and not validated in independent data sets.…”
Section: Discussionmentioning
confidence: 99%